Real Time Information Management of Nutrition Intervention in earthquake affected 14 priority districts of Nepal including data collection with customized REMO system. - Rijal, Sanjay. (Tufts University. Tisch Library., 2019)
This poster shows the support real time data collection and visualization through dashboard, of emergency nutrition interventions.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy